The Effectiveness of Lactation Massage Using Jasmine Oil on Breast Milk Production Among Post-Cesarean Section Mothers in the Working Area of Sukorame Community Health Center, Kediri City - Septina Rahma Damayanti; Dwi Estuning Rahayu; Susanti Pratamaningtyas; Sumy Dwu Antono (Gayaku Publisher, 2026)
Background: Breast milk production among mothers following cesarean section is often suboptimal due to postoperative pain, limited mobility, anxiety, and fatigue, which can inhibit the lactation process. Non-pharmacological interventions, such as lactation massage using jasmine oil, may help stimulate breast milk production by promoting relaxation and hormonal responses. Objective: To determine the difference in breast milk production before and after lactation massage using jasmine oil among post-cesarean section mothers in the working area of Sukorame Community Health Center, Kediri City. Methods: This study employed a pre-experimental design using a one-group pretest-posttest approach without a control group. A total of 36 post-cesarean section mothers were selected through simple random sampling. The intervention consisted of lactation massage with jasmine oil for 15–20 minutes, administered once daily for three consecutive days. Breast milk production was assessed using an observation checklist before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test. Results: The analysis showed a statistically significant difference in breast milk production before and after lactation massage with jasmine oil (p-value = 0.000; p < 0.05). The intervention was associated with improved breast milk production among post-cesarean section mothers. Conclusion: Lactation massage using jasmine oil is effective in improving breast milk production among post-cesarean section mothers. The intervention enhances blood circulation, stimulates prolactin and oxytocin secretion, and provides a relaxing effect. Additionally, the aroma of jasmine oil helps reduce maternal anxiety and increase comfort, thereby optimizing the milk ejection reflex. Suggestion: Healthcare providers, particularly midwives and nurses, are encouraged to incorporate lactation massage with jasmine oil as a complementary non-pharmacological intervention to support breastfeeding among post-cesarean section mothers. Future studies should employ randomized controlled trial designs with larger sample sizes to further confirm its effectiveness.